METHAPHORICAL MEANING INSIDE TEMBANG DOLANAN - Deasy Yunita Siregar (VISION, 2017)
A language cannot be separated from the background and the origin of the place from which it comes. Language may refer either to the specifically human capacity for acquiring and using complex systems of communication, or to a specific instance of such as a system of a complex communications. It is the expression of thought, with the translation of notion into words being the act of understanding. People usually find metaphor while using language in their communication which changes the real meaning of what someone wants to tell about with the deviated meaning. metaphor is defined as a figurative language which used a word or a phrase referring to a certain object or activity to replace other words or phrases so that there is similarity or analogy between both. As a linguistic device, metaphor can be found in any human language. In this case, I chose to analyze a song entitled Tembang Dolanan ( one of traditional song for the children from Java) Tembang Dolanan have noble values of the national culture. Unfortunately, Tembang Dolanan today get less attention from the government and related agencies. At the end of today's children are less familiar with the song, Tembang Dolanan is less attractive and eroded by age. Tembang Dolanan  means to have fun in their spare time and also as a means of communication that contain educational messages.